Disability in Mental illness : A Neglected issue - Subedi, S.; Shyangwa, P.M. (Journal of Psychiatrists’ Association of Nepal, 2018)
Mental health has been hidden behind a curtain of stigma and discrimination for too long. It is time to bring it out into the open. The magnitude, suffering and burden in terms of disability and costs for individuals, families and societies are staggering. In the last few years, the world has become more aware of this enormous burden and the potential for mental health gains. However, The disability related to mental illness has always been a neglected issue in the parlane of health.